Lincoln takes command : the campaign to seize Norfolk and the destruction of the CSS Virginia - Norder, Steven (Savas Beatie, 2019)
"The first study to detail the important week in March 1862 when, for the first and only time in the country's history, a sitting president took direct control of military forces, land and sea, to wage a campaign with wide-ranging consequences. Abraham Lincoln ordered a beach-landing to capture Norfolk, the shelling of major Confederate installations and defenses, and guiding naval assets that helped capture two important cities (Norfolk and Portsmouth) and the Gosport Navy Yard, the best of its kind along the entire Atlantic seaboard. Based on extensive primary sources, supported by original maps and photos, footnotes, biblio, appendices, and index."--